Economic reforms and privatisation of education in India - Rani, P. Geetha (2008)
An attempt is made in this paper to examine economic reforms and privatisation of education per se and higher education, in particular. Privatisation of higher education in India has emerged in several forms and types. it began to grow during the 1980s, and has mushroomed since the 1990s. In this rapidly changing context, the challenge to public policy on higher education, in India, remains to combine private providers with the continuing responsibility of the governments to guide, regulate, monitor and continue the provision of subsidised higher levels of education with a view to striking a balance between equity and efficiency principles. Privatisation has further trickled down to school and even to basic education as well. A growing demand has allowed and encouraged the expanding share of private sector in secondary education. Above all, privatisation at the school level exacerbates inequality and, hence, increasing reliance on it for expansion would increasingly leave out the low-income groups and produce many regressive effects on society. - Reproduced.
Keywords: Privatization - India; Economic reform - India; Economic reform